Pengaruh Paparan Audio Gelombang Theta dengan Kemampuan Mengingat Mahasiswa Ruang Tutorial 15 dan 16 Fakultas Kedokteran Program Studi Pendidikan Dokter Angkatan 2023 - Ade Bayuh Pratama Saweduling; Jimmy Franky Rumampuk; Fransiska Lintong (Syntax Idea)
Difficulty in remembering is an obstacle in learning, especially because memory plays an important role in storing and processing information. Theta waves (4-7 Hz) are known to support the process of strengthening short-term memory to long-term memory, particularly in the hippocampus, with the potential to be utilized to enhance learning abilities. However, research on the influence of theta wave audio exposure on the memory ability of medical students is still limited. This study aims to explore the influence to develop brainwave-based educational strategies. This study uses an experimental research design employing the Pre-Test and Post-Test with Non-Equivalent Control-Group method by comparing before and after exposure to theta wave audio. It was then analyzed using the parametric T-Paired test. A comparison of memory ability before and after exposure to theta wave audio was conducted on 10 subjects in the intervention group and 10 subjects in the control group, and a significant change in memory ability of 0.002 (p<0.005) was found in the intervention group. There is an effect of theta wave audio exposure on memory ability.